Measuring the total factor productivity for international seaport in South East Asia (ASEAN) - RATIKORN KUMTONG; ANUPHAK SAOSAOVAPHAK; CHUKIAT CHAIBOONSRI (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: The goal of this paper is to quantify the contribution of ports to GDP in three different nations. Singapore’s port, Malaysia’s Bintulu port, and Thailand’s Leamchabang port are the ASEAN ports examined in this paper.Methodology: Cargo throughput (tons) is the output variable, and the four inputs (ship count, vessel handled capacity (DWT: Dead Weight Tonnage), number of employees per terminal, and terminal area) are all described in the published data (m2). The weighted aggregative technique is used to construct inputs and outputs data details.Findings: Progress in port efficiency in Singapore, Malaysia, and Thailand is demonstrated by the findings. Singapore’s port is the most productive of the three and has the least disruption to throughput (TFP).Novelty/Implications: While trade and maritime transport cooperation between Korea and ASEAN has been strengthened, little research has been conducted on analyzing container port efficiency in ASEAN. Since this is the first study of its kind in ASEAN, it can be considered the beginning of port studies in the region. Based on these findings, we can select candidate cities and nations for a port cooperation initiative on a global scale.